Climate factors dominate the spatial variation of forest soil nutrients: a meta analysis - Du, Xiaoxuan; Li, Xinyi; Wang, Jiangfeng; Xu, Jiali; Gao, Jie (Frontiers in Forests and Global Change, 2025)
The management mode of forests has significant impacts on soil nutrients. However, with global changes, there is scant evidence to suggest whether the soil nutrients in planted and natural forests have a consistent response mechanism to environmental changes. Utilizing soil nutrient data from 263 planted forests and 434 natural forests in China, collected through field surveys of 298 forests and literature searches from 2005 to 2020, this study explores the differences in soil nutrients between natural and planted forests and their controlling factors. The results indicate that the soil available phosphorus content in natural forests is significantly higher than in planted forests (p < 0.001), and the soil pH is significantly lower than in planted forests (p < 0.001), while there is no significant difference in soil nitrogen content between the two (p > 0.05). With increases in Mean Annual Temperature (MAT) and Mean Annual Precipitation (MAP), soil available phosphorus content significantly increased, and soil pH significantly decreased (p < 0.001). Stand factors (such as stand age and stand density) have a greater influence on soil nutrients in natural forests than in planted forests. Climate factors contribute the most to the spatial variability of soil nutrients in both planted and natural forests. Compared with climate factors, stand factors and forest key leaf traits (such as leaf area, specific leaf area, leaf nitrogen and phosphorus content) had relatively little effect on soil nutrients in planted and natural forests. Climate factors directly or indirectly affect the soil nutrients of planted and natural forests by influencing stand factors and key leaf functional traits, and their direct effects are greater than their indirect effects. The results of this study demonstrate that forest soil nutrients of different types respond to global change in distinct patterns. In future forest management, special attention should be paid to the differences between artificial forests and natural forests.